Un prince français en Suède. Les stratégies de légitimation dans l’édification de la dynastie Bernadotte (1810-1844) - Lisa Castro (Les Cahiers de Framespa)
The bicentenary of Jean-Baptiste Bernadotte’s accession to the Swedish and Norwegian thrones in 2018 was an opportunity for historians to question the notion of legitimacy of the Bernadotte dynasty. Notwithstanding his election as Crown Prince to the Swedish throne by the Diet of Örebro on August 21, 1810, Jean-Baptiste Bernadotte is mainly known for his role as one of the Marshals of the Empire appointed by Napoleon. His coronation as the ruler of the Kingdoms of Sweden and Norway, founded in 1814, marked the birth of a new dynasty since his son, Oscar I, was designated Crown Prince of the unified Kingdom. As soon as he was elected to the throne, Jean-Baptiste Bernadotte realized the benefits of having his son at his side to legitimize his reign. This article analyses how the Bernadotte dynasty used Oscar I to legitimize its reign and founded a new ruling family in Europe in the early 19th century.